Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2015
DOI: 10.1038/emm.2015.72
|View full text |Cite
|
Sign up to set email alerts
|

Rac-mediated actin remodeling and myosin II are involved in KATP channel trafficking in pancreatic β-cells

Abstract: AMP-activated protein kinase (AMPK) is a metabolic sensor activated during metabolic stress and it regulates various enzymes and cellular processes to maintain metabolic homeostasis. We previously reported that activation of AMPK by glucose deprivation (GD) and leptin increases KATP currents by increasing the surface levels of KATP channel proteins in pancreatic β-cells. Here, we show that the signaling mechanisms that mediate actin cytoskeleton remodeling are closely associated with AMPK-induced KATP channel … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
8
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 51 publications
1
8
0
Order By: Relevance
“…Soon after leptin was found to recruit K ATP channels to the β-cell surface the role of PTEN, which was previously implicated in mediating the effect of leptin on K ATP conductance, was re-examined. In agreement with early studies, inhibition of PTEN’s lipid and phosphatase activities are required for actin remodeling and leptin-induced K ATP channel trafficking [55,56]. However, in contrast to findings by the Ashford lab [23], PTEN inactivation was shown to require phosphorylation by Glycogen Synthase Kinase 3 β (GSK3β) but not Casein Kinase 2 (CK2) [55].…”
Section: Katp Channel Trafficking Signaling Moleculessupporting
confidence: 84%
See 1 more Smart Citation
“…Soon after leptin was found to recruit K ATP channels to the β-cell surface the role of PTEN, which was previously implicated in mediating the effect of leptin on K ATP conductance, was re-examined. In agreement with early studies, inhibition of PTEN’s lipid and phosphatase activities are required for actin remodeling and leptin-induced K ATP channel trafficking [55,56]. However, in contrast to findings by the Ashford lab [23], PTEN inactivation was shown to require phosphorylation by Glycogen Synthase Kinase 3 β (GSK3β) but not Casein Kinase 2 (CK2) [55].…”
Section: Katp Channel Trafficking Signaling Moleculessupporting
confidence: 84%
“…In an effort to elucidate how PTEN inactivation following leptin stimulation leads to actin remodeling, Han et al examined the role of Rac [56], a Rho family small GTPase molecular switch that is known to regulate actin dynamics for vesicle transport [57]. They showed that Rac activity is increased and that this is necessary for the recruitment of K ATP channels to the β-cell surface [56].…”
Section: Katp Channel Trafficking Signaling Moleculesmentioning
confidence: 99%
“…The trafficking of K1 channels to cell surface could also be considered as a novel autocrine negative feedback mechanism for insulin secretion (Han et al, 2015). In this way in MIN6 cells, high glucose and exogenous insulin treatment increase K ATP channels trafficking to the surface, stabilizing the membrane potential and avoiding insulin secretion.…”
Section: Pharmacology Of K Atp Channels In Pancreatic Beta Cellsmentioning
confidence: 99%
“…In β-cells, ATP-sensitive potassium channels (KATP) associate glucose stimulation with membrane depolarization. It was shown that AMPK affects the activity of KATP in β-cells, enhancing their migration to the cell membrane by remodeling the cytoskeleton [19]. The effect of leptin, which inhibits the secretion of insulin, is mediated by AMPK and also associated with increased movement of KATP to the cell membrane [20].…”
Section: Combination Of Metforminmentioning
confidence: 99%